Performance comparison of PID controller on SVC and TCSC to the transmission line - Zulkifli, Shamsul Aizam (2007)
In this paper the common devices where been applied at the transmission line to mitigate the voltage or current sag are Static Var Compensator (SVC) and Thyristor Controller Static Compensator (TCSC). To solve this problem a high response controller is required at the control side. One of the technique is applied the Proportional Integration Derivation (PID) controller, compared to the other controllers due to it simplicity, highly steady state response and less margin error. Here, both Flexible AC Transmission System (FACTS) devices have been applied with the same PID controller in comparing the performance response on the transmission line while having the same industrial load. In determined the response, both transfer functions have been generated and combined with PID controller feedback loop to the transfer function for locate the initial poles and zeros. By changing the poles coordinates the response will change either to have fast response or slow response.